Analysis of Hypertention Prevention Behavior Based on Health Belief Model at Pulau Nasi, Pulo Aceh - Putroe Aliya Ricinta; Farrah Fahdhienie; Putri Ariscasari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Non-communicable diseases (NCDs) are one of the leading causes of disease worldwide and are a significant public health problem. One of the non-communicable diseases is hypertension. hypertension is the leading cause of premature death worldwide with 1.28 billion sufferers out of a total population of 8.05 billion or 16% of people worldwide suffering from hypertension. Objective: To determine whether there is a relationship between hypertension prevention behavior and a person's Health Belief Model in vulnerability, seriousness, benefits, barriers and cues to action in the community of Pulau Nasi, Pulo Aceh District. Method: This research is a quantitative study that uses an analytic design with a cross sectional approach with the chi square test. This research was conducted on Pulau Nasi, Pulo Aceh District within a period of 3 days with a population of rice islanders who did not experience hypertension totaling 81 respondents. Result: The result showed that hypertension prevention behavior with the characteristics of respondents on Pulau Nasi with female respondents in the age category dominating 20-40 years (75.6%), the last education is middle level as much as (58%), married status as much as (100%) which is dominated by the work of housewives as much as (88.9%) with domicile in alue reuyeung village as much as (33.3%). There is a significant relationship between barriers and hypertension prevention behavior in the health belief model with a (p-value 0.045) and Cues to Action with a (p-value 0.040) and there is no significant relationship between perceived vulnerability with a (p-value 0.103), perceived seriousness with a (p-value 0.445), perceived benefits with a (p-value 0.123). Conclusion: There is a relationship between barriees and cues to action on hypertension prevention behavior in Pulau Nasi, Pulo Aceh sub-district.